(untitled) (Bangladesh Heart Journal, 2024)
Background: Wound infection is a global health problem, plays an important role in development of chronicity, delaying wound healing associated with long hospital stay. Objective: This study was aimed to identify the bacterial pathogens present in infected wounds and characterize their resistance profile to the most common antibiotics used in the therapy. Methods: This observational study was conducted from January, 2023 to June, 2023 in a tertiary care hospital in Dhaka, Bangladesh. A total of 220 wound swabs and pus samples were collected from the outpatient and inpatient department of this hospital with skin and soft tissue infection. Samples were inoculated on appropriate media and cultured and the isolates were identified by standard procedure as needed. Antimicrobial susceptibility testing was done by disc diffusion method according to ‘The Clinical Laboratory Standard Institute Guidelines’. Results: Out of 220 cases 165(75%) were Male and 55(25%) were female. Majority of the patients 77(35%) were in the age group of 21-31 years. Of the total 220 isolates, 156(70.91%) were culture positive cases. Among the isolated organisms, predominant bacteria was Pseudomonas spp 76(48.22%) followed by Klebsiella 27(17.31%), Escherichia coli 19(12.18%), Proteus 13(8.33%), Staphylococcus aureus 12(7.69%) and Acinetobacter 9(5.77%). Among the gram negative isolates, Pseudomonas was highly sensitive to colistin(88.15%), followed by piperacillin-Tazobactam(77.63%)and Imipenem(50%) and low sensitivity found in ceftriaxone(14.47%), Amoxiclav(13.16) and Clotrimoxazole (13.16%). Klebsiella found sensitive to colistin (90.47%), Piperacillin-Tazobactam (85.71%), Imipenem (76.19%), Gentamycin (71.43%). Escherichia coli shows low sensitivity to almost all the drug except Imipenem (94.74%), Piperacillin-Tazobactam (84.21%) and colistin(84.21%). Stapylococcus aureus show sensitivity to linezolid (100%), vancomycin (91.67%) and Ciprofloxacin (61.67%). Conclusion: Antibiotic sensitivity pattern of various isolates will guide for appropriate selection of the antibiotic against wound infection and reduce the spread of resistance bacteria. Bangladesh Heart Journal 2024; 39(1): 38-43